Can Women Have Children and a Career? IV Evidence from IVF Treatments - Lundborg, Petter; Plug, Erik; Rasmussen, Astrid Würtz (American Economic Review, 2017)
This paper introduces a new IV strategy based on IVF (in vitro fertilization) induced fertility variation among childless women to estimate the causal effect of having children on their career. For this purpose, we use administrative data on IVF treated women in Denmark. Because observed chances of IVF success do not depend on labor market histories, IVF treatment success provides a plausible instrument for childbearing. Our IV estimates indicate that fertility effects on earnings are: (i) negative, large, and long-lasting; (ii) driven by fertility effects on hourly earnings and not so much on labor supply; and (iii) much stronger at the extensive margin than at the intensive margin.